Safety on peripheries, environment protection 2019-2020: A program realised in cooperation of the Ministry of Agriculture and the Nationwide Civil Self-Defence Organisation under professional support of the National Police Headquarters (Academic Journal of Internal Affairs, 2020)
In Lajosmizse was arranged a professional event as the start of the project realised 2019-2020 in cooperation of the Ministry of Agriculture and the Nationwide Civil Self-Defence Organisation under professional support and supervision of the National Police Headquarters. In the lectures has been presented how important cooperation can be at a historical moment, when due to global challenges and the climate change the natural resources of Hungary, the infields, the drinking water reserves and all natural resources are increasing in value as a pawn of well-being for the people living here. Experts and leaders of institutes in several sectors and at several levels recognised that the targets set can be more effectively and more successfully realised by well organised and well prepared cooperation, It is especially interesting when several participants of common programs show the details by own points of view. In this sense we asked the leaders of all three organisations about the project and its details and they cordially complied with our inquiry.
Keywords: Safety on peripheries; environment protection